Populus root exudates are associated with rhizosphere microbial communities and symbiotic patterns - Li, Mengjie; Song, Zhen; Li, Zhanbiao; Qiao, Rongye; Zhang, Pingdong; Ding, Changjun; Xie, Jianbo; Chen, Yinglong; Guo, Hui (Frontiers in Microbiology, 2022)
Microbial communities in the plant rhizosphere are critical for nutrient cycling and ecosystem stability. However, how root exudates and soil physicochemical characteristics affect microbial community composition in Populus rhizosphere is not well understood. This study measured soil physiochemistry properties and root exudates in a representative forest consists of four Populus species. The composition of rhizosphere bacterial and fungal communities was determined by metabolomics and high-throughput sequencing. Luvangetin, salicylic acid, gentisic acid, oleuropein, strigol, chrysin, and linoleic acid were the differential root exudates extracted in the rhizosphere of four Populus species, which explained 48.40%, 82.80%, 48.73% and 59.64% of the variance for the dominant and key bacterial or fungal communities, respectively. Data showed that differential root exudates were the main drivers of the changes in the rhizosphere microbial communities. Nitrosospira, Microvirga, Trichoderma, Cortinarius, and Beauveria were the keystone taxa in the rhizosphere microbial communities, and are thus important for maintaining a stable Populus microbial rhizosphere. The differential root exudates had strong impact on key bacteria than dominant bacteria, key fungi and dominant fungi. Moreover, strigol had positively effects with bacteria, whereas phenolic compounds and chrysin were negatively correlated with rhizosphere microorganisms. The assembly process of the community structure (keystone taxa and bacterial dominant taxa) was mostly determined by stochastic processes. This study showed the association of rhizosphere microorganisms (dominant and keystone taxa) with differential root exudates in the rhizosphere of Populus plants, and revealed the assembly process of the dominant and keystone taxa. It provides a theoretical basis for the identification and utilization of beneficial microorganisms in Populus rhizosphere.